2013
DOI: 10.1213/ane.0b013e318280e109
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Ropivacaine 0.1% and 0.2% for Continuous Interscalene Block After Shoulder Surgery

Abstract: These results suggest that ropivacaine 0.2% provides more effective analgesia than ropivacaine 0.1% during the first 24 hours for continuous interscalene block after shoulder surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Interscalene Yes 20,98,99,108,116,119,130,131,[145][146][147]153,163,164,173,176,195,427 No 4,5,8,16,[77][78][79][80][81]159,162,[168][169][170][171][172]175,428,429 Recent RCT demonstrated a 2-d continuous interscalene block decreases pain 7 d after major shoulder surgery compared with a single-injection ropivacaine block 176 A recent RCT demonstrated that a supraclavicular infusion is noninferior to an interscalene infusion and reduced the incidence of complete or partial hemidiaphragmatic paresis (analgesia was superior to the interscalene catheters in the recovery room) 427 Cervical paravertebral No 6 Little published since the widespread adoption of ultrasound-guided catheter insertion Intersternocleidomastoid No 1 Little published since the widespread adoption of ultrasound-guided catheter insertion Supraclavicular Yes 427 No 77,165,430 Relatively rare catheter site relative to the interscalene location for shoulder surgery Infraclavicular provides superior analgesia to both supraclavicular 432 and axillary 433 catheters for hand, forearm, and el...…”
Section: Shoulder and Proximal Humerusmentioning
confidence: 99%
“…Interscalene Yes 20,98,99,108,116,119,130,131,[145][146][147]153,163,164,173,176,195,427 No 4,5,8,16,[77][78][79][80][81]159,162,[168][169][170][171][172]175,428,429 Recent RCT demonstrated a 2-d continuous interscalene block decreases pain 7 d after major shoulder surgery compared with a single-injection ropivacaine block 176 A recent RCT demonstrated that a supraclavicular infusion is noninferior to an interscalene infusion and reduced the incidence of complete or partial hemidiaphragmatic paresis (analgesia was superior to the interscalene catheters in the recovery room) 427 Cervical paravertebral No 6 Little published since the widespread adoption of ultrasound-guided catheter insertion Intersternocleidomastoid No 1 Little published since the widespread adoption of ultrasound-guided catheter insertion Supraclavicular Yes 427 No 77,165,430 Relatively rare catheter site relative to the interscalene location for shoulder surgery Infraclavicular provides superior analgesia to both supraclavicular 432 and axillary 433 catheters for hand, forearm, and el...…”
Section: Shoulder and Proximal Humerusmentioning
confidence: 99%
“…First, it may be that medication dose/mass is the primary determinant of administration effects, as has been reported for interscalene, 30 femoral, 31 posterior lumbar plexus (psoas compartment), 31 and popliteal perineural catheters. 32 This would explain why a previous study reported a larger cephalad-caudad cutaneous effect with the use of a 0.6 mL/kg bolus of levobupivacaine 0.125% compared with a bolus of half this volume—it was not the higher volume but rather the higher dose responsible for the differing results.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of open shoulder surgery, continuous ISBP analgesia required a basal infusion to provide effective pain relief, with a basal infusion of 5 ml/h [ 20 21 ]. Reducing the basal infusion from 8 to 6 ml/h resulted in similar clinical efficacy in shoulder surgery with ISBPB [ 7 ].…”
Section: Discussionmentioning
confidence: 99%